Sistem Peringatan Dini Banjir Dengan Menggunakan ESP32 dan Sensor Ultrasonik - Mohammad Danu Iswara; Slamet Raharjo (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2026)
The advancement of Internet of Things (IoT) technology has driven its application across various sectors, including flood disaster mitigation. At present, most flood monitoring activities are still conducted manually, resulting in delayed response actions. This research proposes the design of an Android-based flood early warning system utilizing the ESP32 microcontroller as the central controller. The system is equipped with an HC-SR04 ultrasonic sensor to measure water level with high accuracy, a buzzer for local alert signaling, and a Wi-Fi connection to send real-time notifications to an Android application. The operational mechanism begins with the sensor measuring the water surface distance, which is then compared to a predefined threshold. If the water level exceeds this limit, the system activates the alert and sends a notification to the user. This prototype is designed to deliver timely, accurate, and easily accessible information, enabling communities to take preventive measures promptly to minimize the impact of flooding.